FAKTOR-FAKTOR YANG MEMPENGARUHI FINANCIAL STRENGTH INDUSTRI MANUFAKTUR DI INDONESIA - Guntur Suryaputra, Filipus Argentano; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi; Vol 17 No 3 (2016), 2016)
Financial strength caused by external and internal factors.The method of data collecting is purposive sampling method as the purpose of research. T h e study will be used criteria for sampling a company listed on the Indonesia Stock Exchange before 199 3 and has published financial reports for t wo consecutive years, and the company's data available complete. From 141 companies listed in Indonesia Stock Exchange there are 59 companies that meet the criteria and used as a sample.Measurement of financial strength of the firm is the financial strength indexwhich is the opposite of financial difficulties.Regression analysis use to find empirical evident what’s factors that influence financial strength. T he resul t showed that the ratio of working capital, retained earnings ratio, return on assets and stock prices influence positive and significant on the financial strength. S ales ratio does not affect the ability of a company's financial. The variance of dependent variabel can be explained by independent variable abaut 48.2 percent while the rest explained by other s outside.
Keywords: financial strength, financial distress, financial strength index, external factors, internal factors.